The redox thermodynamics and kinetics of flavonoid rutin adsorbed at glassy carbon electrodes by stripping square wave voltammetry - Aragão Catunda Jr., Francisco Eduardo (2011)
The adsorptive accumulation of rutin (RU) at glassy carbon (GC) electrodes in 10% ethanol + 90% 1 mol dm-3 HClO4 aqueous solution is studied by using cyclic (CV) and square wave (SWV) voltammetries. The Frumkin adsorption isotherm best described the specific interaction of rutin with carbon electrodes. By fitting the experimental data, values of -31.9 kJ mol -1 and 0.54 ± 0.02 were obtained for the Gibbs free energy of adsorption and the interaction parameter, respectively. SWV fully characterized the thermodynamics and kinetics of the surface redox process, using a combination of the "quasi-reversible maximum" and the "splitting of SW peaks" methods. Average values of 0.644 ± 0.003 V and 0.44 ± 0.02 were obtained for the formal potential and the anodic transfer coefficient, respectively. Moreover, a formal rate constant of 6.1 × 102 s-1 was obtained. SWV was also employed to generate calibration curves. The lowest concentration of RU experimentally measured for a signal-to-noise ratio of 3:1 was 2 × 10-8 mol dm-3 (12 ppb).